2021
DOI: 10.4235/agmr.21.0063
|View full text |Cite
|
Sign up to set email alerts
|

Geriatrics Fact Sheet in Korea 2021

Abstract: While the global population is aging, South Korea is one of the most rapidly aging societies worldwide. It took 17 years for Korea to transition to an aged society from an aging society, defined as proportions of the population aged 65 years or older of ≥ 14.0% and 7.0%, respectively, while Japan took 24 years for the same transition. 1) More strikingly, Korea is expected to become a super-aged society, defined as a proportion of the population aged 65 years or older of ≥ 20.0%, in 2025. This prominent trend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 32 publications
0
61
2
1
Order By: Relevance
“…Deficit accumulation frailty is defined by the accumulation of illnesses, symptoms, functional and cognitive decline, and socioeconomic status, which are added together to calculate deficit accumulation [ 8 ]. In Korea, the prevalence of frailty in community-dwelling older adults ranges from 7.7% to 17.0% according to frailty phenotype assessment and from 17.5% to 26.3% according to frailty index assessment [ 1 ].…”
Section: Aging and Frailtymentioning
confidence: 99%
See 1 more Smart Citation
“…Deficit accumulation frailty is defined by the accumulation of illnesses, symptoms, functional and cognitive decline, and socioeconomic status, which are added together to calculate deficit accumulation [ 8 ]. In Korea, the prevalence of frailty in community-dwelling older adults ranges from 7.7% to 17.0% according to frailty phenotype assessment and from 17.5% to 26.3% according to frailty index assessment [ 1 ].…”
Section: Aging and Frailtymentioning
confidence: 99%
“…This was attributed to the “baby boom” following World War II and extremely low birth rates in recent years. Korea is expected to become a super-aged society by 2025, defined as a population in which >20% are ≥65 years of age [ 1 ]. Since hematologic malignancy increases with age, older adults represent the growing majority of patients diagnosed with hematologic disorders.…”
Section: Introductionmentioning
confidence: 99%
“… 1 ) AGMR is the leading journal of geriatrics and gerontology in Korea, one of the world’s fastest-aging countries. 2 , 3 ) As population aging has become a dominant demographic trend in East Asian countries, AGMR has also been rapidly growing and establishing its presence in this region. 4 ) AGMR has been publishing articles in English since 2016; since that time, the general volume of submissions has been increasing, and the journal currently has nearly 100% citation growth annually.…”
Section: Introductionmentioning
confidence: 99%
“… 5 ) As the number of older people increases, care demands to serve these populations threaten to overwhelm the Korean health system. Researchers have noted unmet needs for effective management strategies using concepts from geriatric medicine to prevent functional decline in community-dwelling older adults, 6 , 7 ) as the results of early Korean studies have suggested that frailty is a common geriatric condition associated with future adverse health outcomes. 8 , 9 ) However, to our knowledge, when the Aging Study of Pyeongchang Rural Area (ASPRA) was conceptualized in 2014, no longitudinal population-based studies had comprehensively recorded geriatric functional and medical parameters, including frailty and physical performance, in Korea.…”
Section: Introductionmentioning
confidence: 99%